Holistic perspectives for optimizing dietary quality - Phelan, Jessica Mick (Kansas State University, 2023)
The purpose of this dissertation was to use a holistic perspective to better understand overall dietary quality for practical application. Key concepts used to guide each of the studies included “meeting people where they are,” and best practices for maximizing dietary quality. Chapter two, study one, was a critical review that sought to provide a theoretical framework to determine how dietary quality assessment might be translated into practice across different socio-ecological levels to increase the effectiveness of evidence-based practices. A five-step holistic dietary quality assessment process was created to guide public-health officials and clinicians in identifying barriers or facilitators to optimizing dietary quality. In doing so, this study identified potential social and environmental factors that might be present for individuals or populations that affect dietary quality. Examples of these factors include, but are not limited to, food accessibility, socioeconomic status, cultural factors, and food safety/regulation. Study two, chapter three, sought to investigate the potential for maximizing the dietary quality of the most popular “fad diets” in the United States. First a definition of “fad diet” was created, and Google Explore© was used to determine the dietary patterns that were searched for most frequently. Inclusion and exclusion criteria were applied, and nine dietary patterns were included for analysis, where one-week menus were created attempting to maximize dietary quality while staying within the parameters of each fad dietary pattern. Results showed that some of the current popular fad dietary patterns have the potential to achieve a relatively high Healthy Eating Index (HEI) dietary quality score ranging from 77.1-89.1 out of 100 points, potentially surpassing the average American HEI dietary quality score. This study proposed an alternative approach to improving dietary quality by “meeting people where they are.” Ultimately, this type of approach may lead to better adherence and better sustainability of a higher quality diet. Finally, study three, chapter four, was a systematic review that sought to determine the associations between overall dietary quality and the non-clinical mental health outcomes of stress, anxiety, and/or depression among college students, with a secondary aim of determining the association between overall dietary quality and academic performance. Twelve relevant articles met the a priori selection criteria, where ten studies pertained to overall dietary quality and non-mental health outcomes, and two pertained to overall dietary quality and academic performance. The systematic review revealed that very few relevant studies had been conducted that included both non-clinical mental health and academic outcomes in the college student population. Given the prevalence of mental health issues in this population and the intersection between mental health and academic performance, this is an area where research is needed. Results of the meta-analysis indicated weak and moderate associations between overall dietary quality and non-clinical mental health outcomes in college students, and though very limited, based on the two studies included, results showed weak associations with academic performance. Altogether, the three studies included in this dissertation suggest that a holistic paradigm may be beneficial when used to better understand dietary quality for practical application. Future research is needed to help to elucidate the factors that should be considered when working toward improving the quality of the dietary intake of individuals and populations.
Keywords: Dietary quality; Holistic; Dietary quality index